Peripheral mechanisms of peripheral neuropathic pain - Pacifico, Paola; Coy-Dibley, James S.; Miller, Richard J.; Menichella, Daniela M. (Frontiers in Molecular Neuroscience, 2023)
Peripheral neuropathic pain (PNP), neuropathic pain that arises from a damage or disease affecting the peripheral nervous system, is associated with an extremely large disease burden, and there is an increasing and urgent need for new therapies for treating this disorder. In this review we have highlighted therapeutic targets that may be translated into disease modifying therapies for PNP associated with peripheral neuropathy. We have also discussed how genetic studies and novel technologies, such as optogenetics, chemogenetics and single-cell RNA-sequencing, have been increasingly successful in revealing novel mechanisms underlying PNP. Additionally, consideration of the role of non-neuronal cells and communication between the skin and sensory afferents is presented to highlight the potential use of drug treatment that could be applied topically, bypassing drug side effects. We conclude by discussing the current difficulties to the development of effective new therapies and, most importantly, how we might improve the translation of targets for peripheral neuropathic pain identified from studies in animal models to the clinic.